Sedimentation stability of fuel slurries under influence of vibration and centrifugal forces; Chemical Engineering Research and Design; Vol. 215 - Verkhodanov D. A. Danila Andreevich; Piskunov M. V. Maksim Vladimirovich; Romanov D. S. Daniil Sergeevich; Strizhak P. A. Pavel Alexandrovich (2025, 2025)
Title screen